Factors Affecting Job Satisfaction among Secondary School Teachers in Wad-Madeni Greater Locality, Gezira State, Sudan (2020) - Masaad, Osman Tag Elsir; Ahmed, Adel Ali (The journal of contemporary issues in business and government, 2021)
The study aimed to know the most critical factors affecting job satisfaction among secondary school teachers in Wad-Madeni Greater Locality, Gezira state, Sudan (2020), and the study mainly depended on primary data from Wad-Madeni greater locality, Gezira state. A structured questionnaire was used for data collection, and statistical packages were used in the processing and analysis of data. In this study, the researchers applied descriptive statistics; likers scale measurement, and factor analysis. The result shows that the average of age, training courses, experience for males respectively 49.54, 3.36 and 24.04 while for the females 43..05, 2.56 and 17.29. There is a significant difference between males and females in (Residence, Marital status), while the (Education Level, Department, Work is Satisfactory) are not significant. According to Likers scale measurement, the researchers found that most of the respondents in section one (To some extent). In section two, most of the respondents (disagree and strongly disagree). In section three (To some extent) is the answer of most of them. Finally, in the last section also most of them (To some extent). Kaiser standard detected nine factors with roots value higher than 1.0. These nine factors explain 66.528%% of the total variation. The first factor contributes to 15.762%. The second factor contributes by 13.035% of the total variance. The third factor contributes by 6.996%. Factor four contributes by 6.990%. Factor five contributes by 5.621%. Factor six contributes by 5.160%. Factor seven contributes by 4.937%. Factor eight contributes by 4.030%, while the last factor contributes by 3.980% of the total variance. The most important recommendations of this paper are, the number of students must be proportional to the capacity of the classes and must be clear policies and guidelines for incentives and promotions.